2014
DOI: 10.5296/ijele.v2i2.6266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Teaching Academic Text Cohesive Devices on ESL Undergraduates’ Listening Comprehension

Abstract: This paper reports on a study investigating the effects of teaching academic text cohesive devices on ESL students' listening comprehension. The main objective of the study was to find out if through teaching cohesive devices would enhance students' prior knowledge and subsequently result in increased listening comprehension. Based on a pre-test post-test research design, 40 students enrolled in English for Academic Purposes course at a university in Malaysia were engaged as participants. A listening comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The majority of the studies were carried out in the field of writing and reading. Tahsildar & Yusoff (2014) and Japeen's et al (2013Japeen's et al ( , 2014 studies showed that cohesive devices had a positive effect on learner's ability to comprehend English. Dukta's (1979) study reported positive and significant relationship between total substitution scores and reading scores.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The majority of the studies were carried out in the field of writing and reading. Tahsildar & Yusoff (2014) and Japeen's et al (2013Japeen's et al ( , 2014 studies showed that cohesive devices had a positive effect on learner's ability to comprehend English. Dukta's (1979) study reported positive and significant relationship between total substitution scores and reading scores.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to (Mu, 2006), the knowledge of cohesion and coherence (discourse competence) directly influences reading comprehension. The activation of grammatical competence and discourse competence can contribute to two schemata, namely, linguistic schemata, and formal schemata (Tahsildar & Yusoff, 2014); (Uysal, 2012). The research concerned here developed a model of teaching mahārah al-qirā′ah that lecturer could use to overcome students' weaknesses in certain areas of competence needed for text comprehension and particularly weaknesses in grammatical competence and discourse competence.…”
mentioning
confidence: 99%